2021
DOI: 10.3389/fcell.2020.604030
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory Organ Is Populated by Neutrophils and Macrophages During Early Development

Abstract: The immune system of vertebrates is characterized by innate and adaptive immunity that function together to form the natural defense system of the organism. During development innate immunity is the first to become functional and is mediated primarily by phagocytic cells, including macrophages, neutrophils, and dendritic cells. In the olfactory sensory system, the same sensory neurons in contact with the external environment have their first synapse within the central nervous system. This unique architecture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…In spite of these intriguing observations, few studies have examined the potential for a neural-vascular or peripheral “olfactory neurohaemal organ” within the olfactory sensory system. In zebrafish we have recently described the blood/lymphatic vasculature in the developing olfactory organ (Palominos and Whitlock, 2021 ; Palominos et al, 2021 ) that runs adjacent to the region we previously described as containing cell bodies of the TN-GnRH3 neurons (Whitlock et al, 2003 ; Gopinath et al, 2004 ; Whitlock, 2004 ). In zebrafish, the GnRH3 receptor is present in the adult OE as assayed by immunocytochemistry (Whitlock et al, 2006 ) and the isolation of GnRH3-receptor mRNA from olfactory organ tissues (Corchuelo et al, 2017 ).…”
Section: Gnrh Cells: Neuromodulatory Network Originating In the Olfac...mentioning
confidence: 91%
See 1 more Smart Citation
“…In spite of these intriguing observations, few studies have examined the potential for a neural-vascular or peripheral “olfactory neurohaemal organ” within the olfactory sensory system. In zebrafish we have recently described the blood/lymphatic vasculature in the developing olfactory organ (Palominos and Whitlock, 2021 ; Palominos et al, 2021 ) that runs adjacent to the region we previously described as containing cell bodies of the TN-GnRH3 neurons (Whitlock et al, 2003 ; Gopinath et al, 2004 ; Whitlock, 2004 ). In zebrafish, the GnRH3 receptor is present in the adult OE as assayed by immunocytochemistry (Whitlock et al, 2006 ) and the isolation of GnRH3-receptor mRNA from olfactory organ tissues (Corchuelo et al, 2017 ).…”
Section: Gnrh Cells: Neuromodulatory Network Originating In the Olfac...mentioning
confidence: 91%
“…Previously we have shown that zebrafish can make and maintain memories of odors experienced as juveniles and that this “olfactory imprinting” is associated with transcriptional changes within the olfactory organs (Harden et al, 2006 ; Whitlock, 2006 ; Calfun et al, 2016 ). The subsequent analysis of olfactory organ cell types led to the discovery of local neutrophils and macrophages/microglia in the olfactory organs of developing and adult zebrafish (Palominos and Whitlock, 2021 ; Palominos et al, 2021 ; Figure 2B ). These observations build on previous data showing the intimate association between the olfactory sensory and immune systems with macrophages and/or microglia in cultures of olfactory mucosa (Pixley, 1996 ), the major histocompatibility complex class I (MHCI) in the olfactory placode of the mouse (Chacon and Boulanger, 2013 ), and recombination activating gene (RAG) gene expression in the intact OE of zebrafish (Jessen et al, 2001 ).…”
Section: Olfactory-immune Link Underlying Behaviorsmentioning
confidence: 99%
“…In comparison to macrophage dominant tissue niches lung innate immune niche is predominated by neutrophils ( Figure 3C ). Analogous to this role recently phagocytic populations including neutrophils and macrophages were detected in sensory olfactory organ of zebra fish and both phagocytic population play important roles in lifelong neurogenesis of olfactory epithelia ( Palominos and Kathleen, 2021 ). Though macrophages have longer residence times in tissues, neutrophils also have been shown to co-adapt to tissue microenvironments and cater to tissue specific functions and support organ homeostasis highlighting their non-canonical roles beyond infection immunity.…”
Section: Resident Immune Cells In Tissue Microenvironments: Roles In ...mentioning
confidence: 93%
“…Previously we have shown that the lymphatic vasculature (LV) associated with the developing olfactory organs is evident at 14 days post fertilization (dpf) initiating in the ventrolateral side of the organ (Palominos and Whitlock, 2020). To better understand the LV system in the olfactory sensory system of the adult we dissected brains, with olfactory organs attached, from Tg(lyve1b:EGFP;OMP:RFP) animals (Fig.…”
Section: The Adult Olfactory Sensory System Has Extensive Lymphatic Vasculaturementioning
confidence: 99%
“…We have shown that neutrophils populate the developing olfactory organ and use the blood vasculature to migrate to the olfactory organ in response to injury (Palominos and Whitlock, 2020). With the recent re-discovery of the CNS lymphatics in mammals and zebrafish (Bower and Hogan, 2018; Louveau et al ., 2015), we examined the extent of lymphatic vasculature in the adult olfactory organs and its association with blood vasculature.…”
Section: Introductionmentioning
confidence: 99%